(3GdCMcGe aj GdfLhes - (3CHh SYjO Hf efUhQ Hf Ydj HfOGQ GdOGeZGfjs ((3YHO GdQRGb Hf CMeO Hf eMeO GdHZOGOi s)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf MeO GdTGcQjf eLehY CbGhjd GdMceGA GdefLejf GdbOeGA efge hGdeMOKjf ai CMcGe JMGhjd Sfi GdehGdjO s
(3BNQgG (B:s
(3hGfJgi GdTgQ Edi SYJ GdSYhO jOd Ydi Gd NjQ Je GdcJGH s
(3HgG fXGe GdJYbjHIs
(3cJHg GdfGSN dNRGfI CHh GdMSf Ydi Hf fUjQ GdOjf GdSWhSs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI Ydi (B(1112) s
Keywords: (3Gdadcs